Phytochemical study of Dryobalanops from Malaysian Dipterocarpaceae, and structure - activity relationship studies / Agustono Wibowo - Wibowo, Agustono (Institute of Graduate Studies, UiTM, 2014)
distributed as major species in emergent canopy of Lambir Forest and Sarawak lowland dipterocarps forest. The genus is very unique, as there are only seven species available in the whole world, which confined to the tropical forests of West Malesia. The chemical constituents of Dipterocarpaceae are reported to possess various biological activities such as cytotoxicity, antiviral, antibacterial and anti-inﬂammatory activities. The aims of this study are to isolate secondary metabolites, to determine their antibacterial, DPPH scavenging and cytotoxic activities, to study structure-activity relationship, and to propose biogenesis pathway and chemotaxonomic significance in Dryobalanops. The dried powder of the stem bark of D. aromatica, D. lanceolata, D. rappa and D. becarii were macerated with acetone and evaporated under reduced pressure. The crude acetone extract was subjected to vacuum liquid chromatography to give several fractions.